Time-Periodic Solution of the Weakly Dissipative Camassa-Holm Equation - Chunyu Shen (International Journal of Differential Equations)
This paper is concerned with time-periodic solution of the weakly dissipative Camassa-Holm equation with a periodic boundary condition. The existence and uniqueness of a time periodic solution is presented.